Proposta de indicadores de sustentabilidade para avaliação da coleta seletiva de João Pessoa-PB - Sá, Ana Cecília Novaes de (2021)
Sustainability indicators are promising tools for assessing and monitoring a system, being able to provide information that makes it possible to identify progress and setbacks. In this sense, the present study sought to analyze the performance of the selective collection program in the city of João Pessoa-PB, through sustainability indicators. Twenty-eight (28) indicators were previously selected in the bibliographic review stage and 4 indicators were built, totaling 32 indicators that were grouped in the following dimensions: political / institutional, economic, social, environmental, picker's health and safety and disasters, epidemics and pandemics. The preliminary matrix followed for validation by the Delphi Method, in which two rounds were established in order to reduce uncertainties and determine the most relevant indicators for the study. In these steps, the experts assessed the degree of importance of the indicators, using the 5-point Likert scale, and the agreement with the gradations established for each trend towards sustainability. Subsequently, the final matrix was applied to the selective collection program of João Pessoa-PB, to determine the Degree of Sustainability (GS). The validation step resulted in 24 final indicators, 7 of which were political / institutional, 3 economic, 3 social, 4 environmental, 2 of the health and safety of the collector and 5 of the dimension disasters, epidemics and pandemics. The degree of sustainability found for the system was 3.7, indicating low sustainability of the program. The results show that the selective collection of the municipality is vulnerable in the environmental, social and economic aspect, and that the main existing gaps are related to problems of operational, structural, organizational and environmental perception of the population. Despite the gradual progress of the program, investments must be made to promote the sustainability of the system. Thus, it is recommended that the indicators be used continuously by managers and government officials as an instrument to identify and control the main factors that affect the efficiency of selective collection in the municipality.